دراسة الخطاب التداولي عند الجاحظ في ضوء نظرية الاتصال والتبليغ - معزوز، خيرة Maazouz, Khairah (رابطة الأدب الحديث, 2020)
مع نهاية القرن التاسع عشر وبداية القرن العشرين عرف النشاط اللغوي ظهور نظريات لسانية حديثة غربية المنشأ، تعالج اللغة وقضاياها، حيث ظهرت لسانيات الكلام التي تتجاوز النظرة الإفرادية إلى النظرة التداولية التي تجعل من النص خطابا تواصليا حاملة كل المفاهيم التي تشرح شروط أدائه انطلاقا مما يعرضه الدرس العربي البلاغي ونظرية التبليغ والتواصل. وتحديد الموقع المناسب لإسهامات الغرب في ذلك، خاصة وأن تصوراتهم أصيلة هادفة، وتعرف أن الجاحظ كان أديبا ومبدعا بليغا ومبلغا، حيث درس الخطاب وشروط أدائه وتبليغه للمتلقي، فكان حديثه عن الكلام أو الحدث الكلامي أو القول ومقتضى الحال والفائدة الكلامية أو ما يقصد به هو مقابل لمصطلح التداولية pramatique بالمفهوم الحديث والتي تنطلق من الخصائص الشكلية لعناصر الخطاب أو الكلام من (أفعال-بنى حجاجية-حذف-تكرار..) فهي تركز على الجانب الاتصالي والوظيفي للكلام، وهذا لم يغفله الجاحظ في كتاباته ودراساته اللغوية والأدبية.
By the end of the 19th century and the beginning of the twentieth century, linguistic activity was characterized by the emergence of modern Western linguistic theories, dealing with the language and its issues. The linguistics that transcended the individual view emerged in the deliberative view that makes the text a communicative discourse bearing all the concepts that explain the conditions of its performance. Arab rhetoric and the theory of communication and communication. And to determine the appropriate location for the contributions of the West in this, especially since their perceptions are authentic and purposeful, and know that Al-Jahiz was a writer and a creative and eloquent and amount, where he studied the speech and the conditions of its performance and communication to the recipient, was talking about speech or speech or speech and the case and the benefit of words or what is meant is the equivalent of the term Pragmatique in the modern concept, which stems from the formal characteristics of the elements of speech or speech from (actions-structures of the pilgrims-delete the repetition..) It focuses on the communicative and functional aspect of the speech, and this is not overlooked by Al-Jahiz in his writings and studies of language and literature.
Keywords: اللغة العربية -- الأدب العربي -- النقد الأدبي -- تحليل الخطاب -- الجاحظ، عمرو بن بحر بن محبوب، ت. 255 هـ